2010
DOI: 10.1002/cssc.201000277
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Implications of the Surfactant Effect on the Photochemistry of (Substituted) 4‐Chlorophenols in Water

Abstract: The effect of surfactants (cationic, anionic, and nonionic) on the direct photochemistry of selected chlorophenol antimicrobials in aqueous solution has been investigated. The inclusion of the starting aromatics into micelles markedly directs the reaction towards a cleaner process (mainly photoreduction), contrasting with the variety of processes observed when the irradiation is carried out in neat water. This could have some implications from the environmental point of view because such paths may be significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These authors observed that while in pure water a complex mixture of de-chlorinated products is formed comprising quinones and hydroquinones, in the presence of micelles the main reaction was the photo-reduction to the corresponding phenol with chlorine loss, regardless of the chemical properties of the surfactant employed (Scheme 19). 72 Since the toxicity of phenols is even higher than that of the corresponding chlorinated phenols, the presence of the environment of surfactants together with chlorophenols complicates their natural abatement by solar irradiation.…”
Section: Yield Improvement In Metal Catalyzed Reactionsmentioning
confidence: 99%
“…These authors observed that while in pure water a complex mixture of de-chlorinated products is formed comprising quinones and hydroquinones, in the presence of micelles the main reaction was the photo-reduction to the corresponding phenol with chlorine loss, regardless of the chemical properties of the surfactant employed (Scheme 19). 72 Since the toxicity of phenols is even higher than that of the corresponding chlorinated phenols, the presence of the environment of surfactants together with chlorophenols complicates their natural abatement by solar irradiation.…”
Section: Yield Improvement In Metal Catalyzed Reactionsmentioning
confidence: 99%
“…In past years, an alternative activation of Ar–Cl and Ar–O bonds has been devised by photochemical means and involves the photoheterolytic cleavage of such bonds . Thus, the irradiation in polar solvents of aryl chlorides, sulfonates (triflates and mesylates), and diethyl phosphates substituted with strong (e.g., NMe 2 , OMe, OH) or mild (e.g., t -Bu or n -alkyl) electron-donating groups caused the heterolytic cleavage of the Ar–LG bond and ultimately gave a triplet phenyl cation. Phenyl cations , are highly electrophilic species , that exist in two spin configurations, viz.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiations have been carried out at 254 nm in polar protic media (found suitable for the α,n-DHT generation) [76][77][78][79][80]83] such as MeOH or aqueous methanol by a fixed time of 1 h. In both cases, dechlorinated derivatives 1a and 2a along with the photosubstitution products 1b and 2b were obtained in variable yields. The disappearance quantum yield (Φ -1 ) of these compounds is rather low (< 0.1) and slightly increased in aqueous media [68]. Curiously, when changing the nature of the phenol protecting group, in silyl ether 2 the presence of water mainly drives to the formation of compound 2b.…”
Section: Resultsmentioning
confidence: 99%